Do walking motions enhance visually induced self-motion illusions in virtual reality? - Freiberg, Jacob; Grechkin, Timofey; Riecke, Bernhard E. (IEEE, 2013)
Locomotion interfaces that support physical self-motion in virtual reality facilitate spatial updating, but have relatively high cost and typically require large physical spaces. A better understanding of the illusion of self-motion, or vection, presents a potential solution to this problem. Though circular self-motion illusions induced us- ing only visuals or only walking have been investigated previously, the interaction between these two types has not. We conducted an experiment to examine the additive effects of walking stimuli and visual motion cues on intensity and convincingness of circular vec- tion. Our results indicate a trend towards decreased vection onset time when illusory rotation stimuli were combined. Measures of in- tensity and convincingness were also rated higher for the combined stimulus condition when compared with walking or visual stimuli separately. Consequently, lean and elegant virtual reality interface designs should include both walking and visual stimuli for a com- pelling experience of self-motion.
Keywords: 2-page conference paper; Riecke; Riecke_2013; conferencePapers; iat802; iat802_fall2012; jake-freiberg; multi-modal vection; poster; short conference paper; spatial updating; timofey-grechkin